High-sensitivity humidity response film and application thereof in preparation of mobile soft robot

By using Nafion-aniline black film as the humidity response driver, the problem of insufficient driving speed and controllability of the humidity driver in the prior art is solved, and high sensitivity humidity response and periodic motion are achieved, which is suitable for the design of a variety of mobile software robots.

CN119505447AActive Publication Date: 2025-02-25HEFEI UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411628538.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize humidity as a driving force, resulting in insufficient driving speed and controllability of the humidity driver, and it is difficult to achieve periodic motion without periodic changes in energy input.

Method used

Nafion-aniline black film was used as the humidity response driver, and the Nafion-aniline black solution was prepared, dripped into a film and heated and dried to form a film with high humidity sensitivity. The film bends in a humidity gradient environment and quickly returns to shape when humidity changes to achieve periodic movement of the driver.

Benefits of technology

It realizes high sensitivity humidity response, improves the driving speed and controllability of the humidity driver, can achieve periodic motion without periodic changes in energy input, and is suitable for the design of finger contactless guided rolling robots and Mobius ring robots.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505447A_ABST
    Figure CN119505447A_ABST
Patent Text Reader

Abstract

The invention discloses a high-sensitivity humidity response type film and application thereof in preparation of a mobile soft robot, and belongs to the technical field of flexible driver materials, and a preparation method comprises the following steps: (1) uniformly mixing a Nafion solution and N, N-dimethylacetamide, then adding aniline black, fully stirring, and then carrying out vacuumizing treatment to obtain a Nafion-aniline black solution; and dropwise adding the vacuumized Nafion-nigrosine solution on a glass sheet, heating, drying, and stripping the Nafion-nigrosine film from the glass sheet to obtain the Nafion-nigrosine film. The invention provides a new application of the Nafion-aniline black material, and particularly relates to an application of the Nafion-aniline black material in preparation of a humidity response driver, a finger non-contact guide rolling robot or a Mobius annular robot. The manufactured soft robot can move back and forth and even move in a curvilinear manner through finger non-contact control. And a self-sustained moving robot at a sustained humidity input. And the preparation process is simple, short in flow and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flexible actuator materials, and in particular to a high-sensitivity humidity-responsive film and an application thereof in preparing a mobile soft robot. Background Art

[0002] Flexible smart materials can realize the function of converting external stimuli into mechanical energy, and can directly use it in their own deformation and movement. Using the energy in the environment, soft actuators made of flexible smart materials can achieve motion forms such as bending, winding and even bouncing. Thanks to its simple structure, high degree of freedom and strong environmental adaptability, it is becoming a very important research direction in the field of soft robots.

[0003] In recent years, researchers have made great progress in the areas of high sensitivity, large deformation, and robustness. However, a major difficulty is how to effectively utilize humidity, a relatively weak and difficult-to-control stimulus compared to light, heat, magnetism, and other stimuli. Although a considerable number of results on humidity actuators have been published, there is still a lot of room for improvement. Whether it is the driving speed or controllability, there are currently many areas that can be optimized. In particular, it is urgent to develop soft robots that can rely on their own structures to produce periodic motion under non-periodic energy input. The introduction of a series of work will undoubtedly help flexible smart materials develop towards practical applications.

[0004] The Chinese patent application document with publication number CN118623833A discloses a method and application of preparing a programmable humidity actuator by coating with an ink marker. Specifically, the prepared MXene dispersion is filtered to obtain a MXene film, and then a commercial oily marker is used to evenly coat the oily ink on one side of the MXene film to obtain a MXene-oily ink double-layer film humidity actuator. This actuator uses the oxygen-containing groups in the extremely hydrophilic MXene material to interact with water molecules to expand, while the oily ink side does not interact with water molecules, thereby forming a volume mismatch between the two layers, and the entire film bends toward the ink side. On this basis, the pure MXene film is cut with a laser, and the oily ink is coated at the specified position to obtain a programmable humidity actuator. That is, only the double-layer area coated with ink is bent. However, this patent does not involve Nafion-aniline black materials, and does not involve the application of mobile robots.

[0005] The Chinese patent application document with publication number CN117429103A discloses a light-driven film that utilizes light-responsive deformation and its application in bionic actuators and photoelectric conversion friction nanogenerators. Specifically, the Nafion polymer film mixed with black pigment can produce a photothermal conversion effect under light, while utilizing the PE film combined on the other side to generate thermal expansion. The volume mismatch caused by the expansion degree on both sides causes bending toward the Nafion-black pigment side under light. On this basis, the anisotropic mechanical properties of PE are utilized to develop light actuators with various functions. Although the patent mentions Nafion-aniline black material, it is only used in the field of light-driven membranes and photoelectric conversion friction nanogenerators, and is not used in the field of humidity-responsive drive. Summary of the invention

[0006] The technical problem to be solved by the present invention is how to propose a new use of Nafion-nigrosine material.

[0007] The present invention solves the above technical problems through the following technical means:

[0008] The first aspect of the present invention proposes the use of Nafion-aniline black film in the preparation of humidity responsive actuators, finger non-contact guided rolling robots or Mobius ring robots.

[0009] Preferably, the method for preparing the Nafion-aniline black film comprises the following steps:

[0010] (1) preparing a Nafion-nigrosine solution: mixing a Nafion solution and N,N-dimethylacetamide (DMAC) evenly, adding nigrosine, stirring thoroughly, and performing a vacuum treatment to obtain a Nafion-nigrosine solution;

[0011] The mass ratio of the Nafion solution, N,N-dimethylacetamide (DMAC), and nigrosine is 9:3:0.1;

[0012] (2) Preparation of Nafion-aniline black film: dropping a vacuumed Nafion-aniline black solution onto a glass sheet and heating it, and then peeling off the Nafion-aniline black film from the glass sheet after drying to obtain a Nafion-aniline black film having a thickness of 20 to 28 μm.

[0013] Preferably, in step (1), a vortex mixer is used for uniform mixing, and the mixing time is 3-5 hours, more preferably 4 hours.

[0014] Preferably, the vacuuming time in step (1) is 20-40 min, more preferably, 30 min.

[0015] Preferably, the heating temperature in step (2) is 40-60° C., and the heating time is 2-4 h, more preferably, 50° C., 3 h.

[0016] Preferably, the thickness of the Nafion-aniline black film in step (2) is 23 μm.

[0017] The second aspect of the present invention provides a finger-non-contact guided rolling robot, which is obtained by cutting the above-mentioned Nafion-aniline black film into rectangular films and then connecting the head and tail ends; the finger-non-contact guided rolling robot can roll when a finger approaches.

[0018] Preferably, the Nafion-aniline black film is cut into (50-60)×(8-15) mm, and the head and tail ends are bonded with PP tape, and the bonded portion is (3-5)×(8-15) mm.

[0019] The third aspect of the present invention provides a Möbius ring robot, which is obtained by cutting the above-mentioned Nafion-aniline black film into rectangular films, twisting the rectangular films 180°, and then connecting the head and tail ends; the Möbius ring robot can perform continuous circular motion in a humidity environment that is transmitted vertically upward.

[0020] Preferably, the Nafion-aniline black film is cut into (60-70)×(3-5) mm, and the head and tail ends are bonded with PP tape, and the bonded portion is (2-4)×(3-5) mm.

[0021] The beneficial effects of the present invention are:

[0022] 1. The present invention proposes a new use of Nafion-aniline black material, specifically its use in the preparation of humidity-responsive actuators, finger-free contact-guided rolling robots or Mobius ring robots. Since the anionic groups inside the Nafion-aniline black film can form hydrogen bonds with the strong interaction between water, it has a strong attraction to water. At the same time, thanks to the loose and porous structure inside the film, the film has a strong water storage function and a water diffusion function. Therefore, in an environment with a certain humidity gradient, the film can produce rapid humidity expansion locally, causing it to bend toward the side with less humidity. When away from a high humidity environment, the film can quickly restore its shape. Due to the characteristics of the single layer, both sides of the film can respond to the humidity gradient environment. The purpose of rapid response to humidity is achieved, and it has the advantages of fast driving speed and simple structure.

[0023] 2. The present invention prepares a humidity actuator with ultra-high humidity sensitivity and a highly controllable mobile robot, which can be made to move forward and backward or even in a curve through non-contact manipulation. And a self-sustaining mobile robot under continuous humidity input. And the preparation process is simple, the process is short, and the cost is low.

[0024] 3. For the finger-free contact-guided rolling robot, due to the effect of the ring bonding, the local bending of the Nafion-aniline black film will be transformed into a convex effect in the direction of humidity. Therefore, during the deformation process, the center of gravity of the ring robot will move forward in the direction provided by humidity, and rolling will occur. The fingers can provide the local humidity gradient stimulation required by the ring robot, thus guiding the movement of the ring robot.

[0025] 4. For the Möbius ring robot, due to the design of the Möbius ring, the humidity bending of the Nafion-aniline black film will be converted into its own rotation, thereby interacting with the ground and driving itself to produce a circular motion. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the preparation of Nafion-aniline black film in Example 1 of the present invention.

[0027] Figure 2 This is a cross-sectional scanning electron microscope image of the Nafion-aniline black film in Example 1 of the present invention.

[0028] Figure 3 This is a performance test diagram of the humidity response driver in Example 1 of the present invention.

[0029] Figure 4 This is a schematic diagram of a finger-non-contact guided rolling robot in Example 1 of the present invention.

[0030] Figure 5 This is an optical photograph of the finger-non-contact guided rolling robot in Example 1 of the present invention.

[0031] Figure 6 Schematic diagram of the Möbius ring robot in Example 1 of the present invention, wherein A is a schematic diagram of the motion principle and B is a schematic diagram of the motion trajectory.

[0032] Figure 7 This is an optical photograph of the Möbius ring robot in Example 1 of the present invention.

[0033] Figure 8 This is a tensile curve diagram of films with different aniline black contents in Example 2 of the present invention.

[0034] Fig. 9 This is a performance test curve diagram of the humidity actuator with different aniline black contents in Example 3 of the present invention.

[0035] Fig.10 It is a performance test diagram of films with different DMAC solutions or film thicknesses in Example 4 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0038] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0039] The embodiments of the present invention specifically use Nafion and nigrosine (water-soluble) materials as the objects to introduce their preparation processes. Other Nafion materials using the preparation processes of the present invention should also be within the scope of protection of the present invention. The embodiments of the present invention specifically use the D520 membrane solution produced by Dupont as the base membrane. Other base membranes in the prior art, such as Flemion membrane of Asahi Glass, Aciplex membrane of Asahi Chemical, or Aquivion membrane of Solvay Solexis, should also be within the scope of protection of the present invention.

[0040] Embodiment 1:

[0041] The preparation method of Nafion-aniline black film comprises the following steps:

[0042] (1) Preparation of Nafion-nigrosine solution: 4.5 g Nafion, 1.5 g DMAC solution and 0.05 g nigrosine (water-soluble) dye powder were mixed and stirred for 4 h using a vortex mixer. Then, the mixture was vacuumed for 30 min to obtain a Nafion-nigrosine solution having a nigrosine content of 0.8% by mass.

[0043] (2) Preparation of Nafion-aniline black film: Use a pipette to take 2 mL of the prepared Nafion-aniline black solution and drop it onto a 75×25 mm glass slide, then use a heating platform and set it to heat at 50°C for 3 h. Place the glass slide with the Nafion-aniline black film in deionized water. After 5 seconds, the film falls off the glass slide. Use a glass slide to transfer the film from the water to filter paper. After removing the water, cut off the edge area with a width of 2 mm to obtain the Nafion-aniline black film. (Schematic diagram of the preparation process is shown in the figure) Figure 1 As shown, the process of preparing this Nafion-aniline black film from solution to drop casting and drying into a film is demonstrated)

[0044] The cross-sectional view of the obtained Nafion-aniline black film after scanning electron microscopy is shown in the figure below: Figure 2 As shown, it can be seen that its thickness is approximately 23 μm, and a porous structure is created therein that is conducive to the absorption and diffusion of moisture, thereby promoting its rapid response to humidity.

[0045] The Nafion-aniline black film prepared in this example is used to prepare a humidity-responsive actuator, a finger-non-contact guided rolling robot or a Mobius ring robot:

[0046] Preparation of Nafion-aniline black humidity responsive actuator: Cut the dried Nafion-aniline black film into 30×10 mm rectangular films, adhere one end to a glass substrate with artist tape, and reserve 20×10 mm at the free end.

[0047] Build a humidity-driven test platform: Use a heating platform to heat water to provide a humidity gradient environment, and cover it with a stainless steel mesh (400 mesh) to support the glass substrate and the driver connected to it, with a height of 10 mm from the liquid surface.

[0048] The humidity response actuator was used to test the bending angle and bending speed. The test results are shown in Figure 3 As shown in the figure, it can be seen that "△RH" is the relative humidity difference, which is the value of the surface humidity of the stainless steel mesh minus the air humidity. The humidity actuator can produce a bending angle of more than 180° when the relative humidity difference is 40%, and has an extremely fast deformation speed of 205° / s.

[0049] Preparation of finger-non-contact guided annular rolling robot: Cut the dried Nafion-aniline black film into rectangular films of 55×10 mm, and adhere the ends with PP tape, with the adhered part of 4×10 mm.

[0050] The rolling test of the finger-free guided circular rolling robot was conducted: the finger was placed 5 mm above the soft robot, causing it to bend and deform toward the finger, while the finger slowly moved forward. When the center of gravity offset was sufficient for the soft robot to roll, the soft robot rolled. Repeating the steps could make the soft robot roll toward the finger continuously. Figure 4 As shown in the figure, when a finger approaches the rolling robot, the moisture of the finger acts on the local surface of the soft robot, and the moisture is transferred from the finger to the local surface and diffuses inward. As a result, different degrees of humidity expansion are generated in the normal section, resulting in a convex bend toward the finger. As the degree of bending increases, the center of gravity of the entire ring shifts, and when the shift is large enough, the soft robot will roll. Repeating this process can make the soft robot roll toward the finger all the time.

[0051] Optical photos of the finger-free guiding rolling robot to perform straight-line rolling and slope rolling. Figure 5 As shown in the figure, it can be seen that under the guidance of the finger, the soft robot rolls towards the finger at a speed of about 5mm / s. At the same time, this soft robot can also roll on a surface with certain obstacles and slopes without being guided by the finger.

[0052] Preparation of a Möbius ring self-sustaining motion robot: Cut the dry Nafion-aniline black film into 65×3 mm rectangular films, twist them 180°, and then adhere the ends with PP tape, with the adhered part being 3×4 mm.

[0053] Build a humidity-driven test platform: Use a heating platform to heat water to provide a humidity gradient environment, and cover it with a stainless steel mesh (400 mesh) to support the film, with a height of 10 mm from the liquid surface. Place the film on the stainless steel mesh and heat the water to 38°C.

[0054] The schematic diagram of the Möbius ring robot is as follows Figure 6 As shown in the figure, it can be seen that the Möbius ring robot can generate interaction force by contacting the ground through its own continuous self-rotation in a humidity environment that is transmitted vertically upward, thereby driving itself to produce a circular motion.

[0055] Optical photo of a Mobius ring robot moving on a stainless steel mesh Figure 7 As shown in the figure, it can be seen that the Möbius ring robot continuously produces ring-shaped displacement under humidity stimulation. The white curve is the trajectory of its movement.

[0056] Comparative Example 1:

[0057] A Nafion humidity-driven film is prepared, and compared with Example 1, the difference is that no aniline black is added. The rest is the same as Example 1.

[0058] Comparative Example 2:

[0059] The difference between this comparative example and Example 1 is that in step (1), the amount of nigrosine is 0.025 g, and a Nafion-nigrosine solution with a nigrosine content of 0.4% by mass is obtained. The rest is the same as Example 1.

[0060] Comparative Example 3:

[0061] The difference between this comparative example and Example 1 is that in step (1), 0.075 g of nigrosine is used to obtain a Nafion-nigrosine solution with a nigrosine content of 1.2% by mass. The rest is the same as Example 1.

[0062] Comparative Example 4:

[0063] The difference between this comparative example and Example 1 is that the mass of the DMAC solution is 0.8 g, and the rest is the same as Example 1.

[0064] Comparative Example 5:

[0065] The difference between this comparative example and Example 1 is that the mass of the DMAC solution is 3 g, and the rest is the same as Example 1.

[0066] Comparative Example 6:

[0067] The difference between this comparative example and Example 1 is that the thickness of the Nafion-aniline black film is 17 μm, and the rest is the same as Example 1.

[0068] Comparative Example 7:

[0069] The difference between this comparative example and Example 1 is that the thickness of the Nafion-aniline black film is 35 μm, and the rest is the same as Example 1.

[0070] Embodiment 2:

[0071] 30×10 samples of the films prepared in Example 1 and Comparative Examples 1 to 3 were taken for tensile mechanical property testing. Figure 8 .

[0072] Wherein Nafion is the Nafion humidity-driven film prepared in Comparative Example 1, AB-Nafion 0.8 is the AB-Nafion film sample prepared in Example 1, AB-Nafion 0.4 is the AB-Nafion film sample prepared in Comparative Example 2, and AB-Nafion 1.2 is the AB-Nafion film sample prepared in Comparative Example 3.

[0073] pass Figure 8 The test results show that the brittleness of the humidity-driven film increases after adding the nigrosine solution. The elastic modulus of the Nafion humidity actuator of Comparative Example 1 without adding nigrosine is decreased in Comparative Example 2 and 3, and the Nafion-nigrosine film in Comparative Example 3 becomes more fragile and difficult to be prepared into a mobile robot.

[0074] Embodiment 3:

[0075] The humidity-driven bending performance test was performed on the humidity-driven actuators prepared in the above-mentioned Example 1 and Comparative Examples 1 to 3. The test results are shown in Fig. 9 .

[0076] pass Fig. 9 According to the performance test analysis, the Nafion-aniline black film prepared in Comparative Example 3 has the fastest driving speed and the largest humidity driving angle because of the higher amount of aniline black added and the lower elastic modulus. The performance of the actuator obtained in Example 1 is second. The film prepared in Comparative Example 3 and Comparative Example 1 has the worst performance.

[0077] Embodiment 4:

[0078] The performance of the films obtained in Example 1 and Comparative Examples 4 to 7 was tested and compared with Example 1. The results are as follows: Fig.10 As shown in the figure, it can be seen that the samples of Comparative Examples 4 and 6 are difficult to form films, and they are broken when peeled off from the glass substrate, making it difficult to apply and test. However, Comparative Examples 5 and 7 can be peeled off from the glass substrate to form complete films.

[0079] However, by subjecting Comparative Examples 5 and 7 to the same humidity performance test as in Example 1, under the condition of a relative humidity difference of 28%, Comparative Example 7 has no advantages in bending angle and bending speed. Although Comparative Example 5 has a larger bending degree than Example 1, its bending speed is far less than that of Example 1. Therefore, in general, Example 1 has better comprehensive performance.

[0080] Embodiment 5:

[0081] The difference between this embodiment and embodiment 1 is that the thickness of the Nafion-aniline black film is 20 μm, and the rest is the same as embodiment 1.

[0082] Embodiment 6:

[0083] The difference between this embodiment and embodiment 1 is that the thickness of the Nafion-aniline black film is 28 μm, and the rest is the same as embodiment 1.

[0084] Embodiment 7:

[0085] The difference between this embodiment and embodiment 1 is that the vacuuming time in step (1) is 20 minutes, the heating temperature in step (2) is 60° C., and the heating time is 2 hours. The rest is the same as embodiment 1.

[0086] Embodiment 8:

[0087] The difference between this embodiment and embodiment 1 is that the vacuuming time in step (1) is 40 minutes, the heating temperature in step (2) is 40° C., and the heating time is 4 hours. The rest is the same as embodiment 1.

[0088] The properties of the films prepared in Examples 5 to 8 are similar to those in Example 1.

[0089] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. Application of Nafion-aniline black film in the preparation of humidity-responsive actuators, finger-guided non-contact rolling robots or Möbius ring robots.

2. The use according to claim 1, characterized in that: The method for preparing the Nafion-nigrosine film comprises the following steps: (1) preparing a Nafion-nigrosine solution: mixing a Nafion solution and N,N-dimethylacetamide uniformly, adding nigrosine dye, stirring thoroughly, and performing a vacuum treatment to obtain a Nafion-nigrosine solution; The mass ratio of the Nafion solution, N,N-dimethylacetamide and nigrosine is 9:3:0.1; (2) Preparation of Nafion-aniline black film: dropping a vacuumed Nafion-aniline black solution onto a glass sheet and heating it, and then peeling off the Nafion-aniline black film from the glass sheet after drying to obtain a Nafion-aniline black film having a thickness of 20 to 28 μm.

3. The use according to claim 2, characterized in that: In step (1), a vortex mixer is used to mix uniformly for a mixing time of 3-5 hours.

4. The use according to claim 2, characterized in that: The vacuuming time in step (1) is 20-40 minutes.

5. The use according to claim 2, characterized in that: The heating temperature in step (2) is 40-60° C. and the heating time is 2-4 h.

6. The use according to claim 5, characterized in that: The heating temperature in step (2) is 50° C. and the heating time is 3 h.

7. A finger-free non-contact guided rolling robot, characterized in that: The method is obtained by cutting the Nafion-aniline black film described in any one of claims 2 to 6 into rectangular films and then connecting the head and tail ends thereof; the finger non-contact guided rolling robot can roll when a finger approaches.

8. The finger non-contact guided rolling robot according to claim 7, characterized in that: The Nafion-aniline black film was cut into (50-60)×(8-15) mm, and the ends were bonded with PP tape, and the bonded part was (3-5)×(8-15) mm.

9. A Möbius ring robot, characterized in that: The method is prepared by cutting the Nafion-aniline black film into rectangular films, twisting the rectangular films by 180 degrees, and then connecting the head and tail ends thereof; the Möbius ring robot can perform continuous circular motion in a humidity environment that is transmitted vertically upward.

10. The Möbius ring robot according to claim 9, characterized in that: The Nafion-aniline black film was cut into (60-70)×(3-5) mm, and the ends were bonded with PP tape, and the bonded part was (2-4)×(3-5) mm.

Citation Information

Patent Citations

  • Method for preparing programmable humidity driver by adopting ink mark pen coating and application

    CN118623833A

  • Method for producing nanoparticles by forced ultra-thin film rotary processing

    CN101795772A

  • Ion exchange membrane type multi-stimulus response flexible driver, preparation method and application

    CN114633530A

  • Temperature and humidity response driver and preparation method thereof

    CN116497527A

  • Optical response deformation CD-ROM drive film, preparation method thereof and application of CD-ROM drive film in bionic driver and photoelectric conversion friction nano-generator

    CN117429103A